Revisiting the Innovation-export Nexus using Industry-level Data: Evidence from China’s Large- and Medium-sized Industrial Enterprises - Rauf, Abdul; Ma, Ying; Jalil, Abdul (International Journal of Economics and Financial Issues, 2019)
The paper aims to provide new evidence about the relationship between technological innovation and industrial export in China. In particular, using a unique industry-level data on a panel of China’s 27 two-digit manufacturing industries over the 1998-2010 period, the study empirically investigates the impact of various aspects of technological innovation on export performance of large- and medium-sized industrial enterprises (LMEs). The results based on a system-GMM estimation report that: First, domestic innovation efforts and foreign investment have a significant positive impact on China’s industrial export performance, whereas the former has a relatively stronger influence on export success than the later; Second, the export growth has benefitted greatly from China’s integration into world trade and the effect of trade openness on export boom is greater than both the domestic and foreign innovation efforts. Further, a recent increase in the scientific and technological development staff has initiated the learning process in LMEs and has put a favourable impact on industrial export. Last, market reforms in china have played a crucial role in manufactured export development through improvement in separate ownership and creation of competitive market. These results are robust to several tests, sensitivity checks and alternative variables on diverse channels for technological innovation. Findings of the paper suggest some policy points for designing China’s new development strategy in an era of sluggish growth. Keywords: Technological innovation, Foreign investment, Indigenous innovation, Market-oriented reforms, Industrial export, China JEL Classifications: F14, F23, O14, O31, O32 DOI: https://doi.org/10.32479/ijefi.7942